Structural Model Explanation of the Relationship Between Early Maladaptive Schemas and Adaptation in Students: The Mediating Role of Coping Strategies - Salari Moghaddam, Leila; Ebrahimi Moghadam, Hossein; Pirani, Zabih (KMAN Counseling & Psychology Nexus, 2024)
Early maladaptive schemas lead to biases in individuals’ interpretations of events, and these biases influence how individuals cope with events and the extent of their adaptation. The aim of the present study was to explain the structural model of the relationship between early maladaptive schemas and adaptation in students, with the mediating role of coping strategies. This was a correlational analytical study. The statistical population of the study included all students enrolled at the Islamic Azad University, Arak Branch, in the first half of 2022. Among them, 443 students were selected using voluntary sampling. The research tools included the Young Schema Questionnaire (1998), the Coping Styles Questionnaire by Folkman and Lazarus (1985), and the Bell Adaptation Questionnaire (1939). Data analysis was performed using path analysis and the software SPSS 24 and Amos 24, with a significance level of 0.05. The results of the study showed that the proposed model had a good fit with the collected data (χ² = 244.65, df/χ² = 3.45, CFI = 0.948, GFI = 0.931, AGFI = 0.898, RMSEA = 0.075). In this study, emotion-focused coping strategies (P < 0.001, β = 0.82) and problem-focused coping strategies (P < 0.001, β = 0.75) significantly mediated the relationship between early maladaptive schemas and adaptation. The findings of the study indicated that there is a significant relationship between early maladaptive schemas and adaptation in students, with problem-focused and emotion-focused coping strategies mediating this relationship.